Blueberry Anthocyanins and Pyruvic Acid Adducts: Anticancer Properties in Breast Cancer Cell Lines - Faria, Ana (2010)
The purpose of this study was to investigate the anticancer properties of an anthocyanin-pyruvic acid adduct extract, which is being developed aiming to be further applied in the food industry. An anthocyanin extract from blueberry (extract I) and an anthocyanin-pyruvic acid adduct extract (extract II) were tested on two breast cancer cell lines (MDA-MB-231 and MCF7). Proliferation was assessed by SRB assay and H-3-thymidine incorporation. Caspase-3 activity was determined in the presence of both extracts. Their capacity as chemoattractants and their invasive potential were also assayed. In both cell lines, extracts I and II significantly reduced cell proliferation at 250 mu g/mL, after 24 h of cell incubation. Caspase-3 activity was not altered by the extracts (250 mu g/mL) in either cell line, with the exception of extract H in MCF-7, which increased its activity, probably explaining its effects on cell proliferation. Both extracts (250 mu g/mL) demonstrated significant antiinvasive potential in both cell lines. Furthermore, they did not demonstrate any capacity for chemotaxis. In conclusion, blueberry anthocyanins and the respective anthocyanin-pyruvic acid adducts demonstrated anticancer properties by inhibiting cancer cell proliferation and by acting as cell antiinvasive factors and chemoinhibitors. The anthocyanin-pyruvic acid adduct extract showed a more pronounced effect in MDA-MB-231, suggesting an effect independent of estrogen receptors. Copyright (C) 2010 John Wiley & Sons, Ltd.